Expression of Green Fluorescent Protein in Aureobasidium pullulans and Quantification of the Fungus on Leaf Surfaces. (October 1997) - Wymelenberg, A.J. Vanden; Cullen, D.; Spear, R.N.; Schoenike, B.; Andrews, J.H.
A red-shifted, mutated form of the jellyfish green fluorescent protein (GFP) under control of a TEF promoter was expressed at high levels in the filamentous fungus Aureobasidium pullulans . In the three transformants studied, all morphotypes of the fungus, including pigmented chlamydospores, expressed GFP and fluoresced brightly. Confocal microscopy showed that the intracellular distribution of GFP was nonuniform. When applied to leaf surfaces, the transformants were readily visible and amenable to quantification by image analysis. Thus, GFP expression, together with quantitative image analysis, may provide a powerful method for ecological studies of plant-microbe relationships in nature.